Answer:
98/76= (rounded to the nearest thousandth) 1.289.
The arrows show the appropriate destination for your dragging.
_____
Combining like terms in the given expression makes it simplify to ...
(2x -18x) +(14y) +(9 -10) = -16x +14y -1
We are to compare this expression with the offered expressions to see if they simplify to the same thing. We'll examine those left-to-right starting with the top row:
- 2x -18x +14y -19 = -16x +14y -19 . . . not the same
- -2xy -1 . . . not the same
- 16x +14y -1 . . . not the same
- 9 -16x +14y -10 = -16x +14y -1 . . . equivalent
- -16x +14y -1 . . . equivalent and simplified
- 2x -18x +14y -1 = -16x +14y -1 . . . equivalent
Answer:
-3
Step-by-step explanation:
(−b)+c=
Let b = -5 and c = -8
- (-5) + -8
5 -8
-3
6/12 is equal to 6 over 12 or .5 or 1/2 when reduced
Answer:
A: False
B: False
C: True
D: True
E: False
F: True
G: True
H: True
Step-by-step explanation:
A: 9(x - 2) = 9x + 2
9x - 18 = 9x + 2 FALSE
B: 65 - y = y - 65
(equation rearranged) -y + 65 = y - 65 FALSE
C: g (times) h = h (times) g (TRUE due to the commutative property of multiplication)
D: a (times) 0 = 0 (TRUE because anything times 0 equals 0)
E: (4 (times) 2) - r = 4 (2 (times) r)
8 - r = 8 - 4r FALSE
F: k + 0 = k TRUE
G: (a + x) + y = a + (x + y)
a + x + y = a + x + y TRUE
H: 5(2x - 9) = 10x - 45
10x - 45 = 10x - 45 TRUE